2001
DOI: 10.1111/1475-4754.00028
|View full text |Cite
|
Sign up to set email alerts
|

Lustre Recipes from A Medieval Workshop in Paterna

Abstract: The discovery of the workshop`Les Olleries Xiques' in Paterna has provided a unique opportunity to analyse the raw materials, and in particular the recipes used in the production of the lustre decorations. Chemical and phase analyses of lustre raw materials and of lustre decorations belonging to the workshop pottery are shown. A comparison with existing ancient documentation on lustre recipes is also presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
70
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(76 citation statements)
references
References 1 publication
5
70
0
1
Order By: Relevance
“…8,9 EIBS measurements were made with the 5 MV tandem accelerator at CMAM. 18 The analysis were performed in vacuum using a 3035 keV He beam in order to take advantage of the elastic resonance 16 O͑␣, ␣͒ 16 O occurring at this energy 19 and which increases the sensitivity to detect oxygen by a factor of 23. The size of the beam was a square of 1 mm diagonal.…”
Section: Materials and Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…8,9 EIBS measurements were made with the 5 MV tandem accelerator at CMAM. 18 The analysis were performed in vacuum using a 3035 keV He beam in order to take advantage of the elastic resonance 16 O͑␣, ␣͒ 16 O occurring at this energy 19 and which increases the sensitivity to detect oxygen by a factor of 23. The size of the beam was a square of 1 mm diagonal.…”
Section: Materials and Techniquesmentioning
confidence: 99%
“…8 and 9 by applying a synthetic raw luster mixture containing 60% illitic clay, 10% CuO, and 30% HgS selected after the archeological findings in the site excavations from the 13th century AD Paterna workshop. 16 Historically, luster nanolayers were developed over glasses and glazed ceramics. Therefore, three different glasses and glazes were selected: a lead glaze ͑glaze-m͒ applied over a white ceramic substrate, a high Na content lead free glaze ͑glaze-a͒ which was also applied to a white ceramic substrate, the final example was actually a lead free glass coverslip from Marienfeld ͑glass-a͒.…”
Section: Materials and Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 Several studies have shown that the lusters consist of a thin surface layer (several hundred nanometers thick) of metal nanoparticles, silver and/or copper with sizes ranging between 2 and 50 nm, randomly distributed within a glassy matrix. [1][2][3][4] The production process [7][8][9] involves first ion exchange between the silver/copper ions (Ag þ /Cu 2þ or Cu þ ) from an initial mixture applied on the glass surface and the alkaline (Na þ and K þ ) ions from the glass, and then the nucleation and growth of metal nanoparticles through reduction of Ag þ to Ag 0 and Cu 2þ /Cu þ to Cu 0 .…”
Section: Introductionmentioning
confidence: 99%
“…There are many different recipes to obtain lustre, depending on the desired color [17,18,19]. Basically all of them contain a metallic element: Ag(I) and/or Cu(II), Fe(III) oxide, a sulfur source (HgS in many cases) and a solid solvent (usually fine clay) to dilute the active components to make easier the handling of the resulting raw pigment powder.…”
Section: Introductionmentioning
confidence: 99%